Inhibitor adsorption processes in mild steel/new bipyrazole derivatives/hydrochloric acid system. (2020) - Bouklah, M.; Daoudi, W.; Hammouti, B.; Touzani, R.; Radi, S.; Ramdani, M.; Bouyanzer, A.; Aouniti, A.; Salghi, R.
Abstract: The corrosion inhibition of mild steel in 1 M hydrochloric acid solution by some bipyrazole derivatives N, N '-dimethyl- N, N '-bis(1 H -pyrazol-1-ylmethyl)ethane-1, 2-diamine (3a ), 1-{[{2-[[(3-carboxy-5-methyl-1 H -pyrazol-1-yl)methyl](methyl)amino]ethyl}(methyl)amino]methyl}-5-methyl-1 H -pyrazole-3-carboxylic acid (3b ) and 1-{[{2-[{[3-(methoxycarbonyl)-1 H -pyrazol-1-yl]methyl}(methyl)amino]ethyl}(methyl)amino]methyl}-1 H -pyrazole-3-carboxylic acid (3c ) has been studied in relation to the concentration of the inhibitors as well as the temperature using chemical (weight loss) and electrochemical (ac impedance and dc polarisation) techniques. All the methods employed are in reasonable agreement. The protection efficiency increases with increasing inhibitors concentration and with increasing temperature. The thermodynamic functions of dissolution and adsorption processes were calculated from weight loss measurement and the interpretation of the results are given. Adsorption of inhibitor on the carbon steel surface is found to obey the Langmuir adsorption isotherm.